1992
DOI: 10.1007/bf01997496
|View full text |Cite
|
Sign up to set email alerts
|

Hyperosmolarity selectively enhances IgE-receptor-mediated histamine release from human basophils

Abstract: Increased osmotic pressure has been reported to cause non-cytotoxic histamine release (HR) from human basophils, as well as a potentiation of HR induced by anti-IgE. In this study, the effects of hyperosmolar Na-K-acetate (300-600 mOsm/kg H2O) on HR was studied in washed human blood cells from newborns, adult volunteers and patients with severe atopic dermatitis. These three patient groups represented 3 very distinct populations with respect to total plasma IgE content, medians were less than 0.2 IU/ml, 20.5 I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Increases in Na + concentration by 40 mM, comparable to levels found in infected or dietary Na + -laden skin, did not interfere with ROS production of N -formyl-methionyl-leucyl-phenylalanine (fMLP)-activated granulocytes and even enhanced the elastase release of fMLP-activated granulocytes [99, 100]. Similarly, enhancing osmolarity with Na + /K + acetate augmented the release of histamine from basophil granulocytes [101]. Whether increased salt concentrations, as found in infected and inflamed skin tissue, affect the subcellular charge balance of phagosomes is as yet unknown (reviewed in [102]).…”
Section: Salt and Other Immune Cellsmentioning
confidence: 99%
“…Increases in Na + concentration by 40 mM, comparable to levels found in infected or dietary Na + -laden skin, did not interfere with ROS production of N -formyl-methionyl-leucyl-phenylalanine (fMLP)-activated granulocytes and even enhanced the elastase release of fMLP-activated granulocytes [99, 100]. Similarly, enhancing osmolarity with Na + /K + acetate augmented the release of histamine from basophil granulocytes [101]. Whether increased salt concentrations, as found in infected and inflamed skin tissue, affect the subcellular charge balance of phagosomes is as yet unknown (reviewed in [102]).…”
Section: Salt and Other Immune Cellsmentioning
confidence: 99%
“…Washed blood cell preparations were made as described in detail previously, as were the normo-and hyper-osmolar Na-K-acetate buffers (300 mOsmAg H2O and 500 mOsm/kg H.O. respectively) (11). A microfibre-based fluorometric histamine release assay was employed, as described previously (10).…”
Section: Histamine Release From Washed Blood Cellsmentioning
confidence: 99%
“…Concomitantly, the effects of hyperosmolarity were studied. Hyperosmolarity was found to increase IgE-mediated release of histamine (11). and due to mechanistic similarities between the actions of phorbol ester and hyperosmolarity, a common mechanism of action has been suggested (26).…”
Section: Histamine Releasementioning
confidence: 99%
“…HR was determined by a microfiber-based method in washed blood cells, as previously described (21,26,28). Briefly, blood samples were washed four times in a Na-K-acetate buffer before resuspension in the original volume.…”
Section: Histamine Release (Hr) Experimentsmentioning
confidence: 99%
“…Previous experiments have shown that the use of a hypertonic Na-K-acetate bufler in HR experiments increased the sensitivity of the HR assay without distorting the concentration responses to IgEmediated stimuli (21). Eor study of the effects of the hypertonic buffer on antigen-induced HR, blood samples from the first 61 consecutive patients were prepared in 500 mOsm/kg H2O buffer (232 mM Naacetate), and 58 blood samples were prepared in a buffer containing 140 mM of Na-acetate(300 mOsm/ kg H3O).…”
Section: Histamine Release (Hr) Experimentsmentioning
confidence: 99%